2017
DOI: 10.1111/pbi.12758
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated targeted mutagenesis of GmFT2a delays flowering time in soya bean

Abstract: SummaryFlowering is an indication of the transition from vegetative growth to reproductive growth and has considerable effects on the life cycle of soya bean (Glycine max). In this study, we employed the CRISPR/Cas9 system to specifically induce targeted mutagenesis of GmFT2a, an integrator in the photoperiod flowering pathway in soya bean. The soya bean cultivar Jack was transformed with three sgRNA/Cas9 vectors targeting different sites of endogenous GmFT2a via Agrobacterium tumefaciens‐mediated transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
144
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(148 citation statements)
references
References 56 publications
2
144
1
1
Order By: Relevance
“…Accelerated maturity in rice and tomato was achieved via knockout of OsHd2 , Hd4 , Hd5 (Li et al ) and of SlSP5G (Soyk et al ), respectively. By contrast, knockout of GmFT2 entailed delayed flowering time in soybean (Cai et al ). Li et al () demonstrated that mutagenesis of the long non‐coding RNA1459 results in delayed tomato fruit ripening.…”
Section: Applications Of Targeted Genome Modification By Nhejmentioning
confidence: 99%
“…Accelerated maturity in rice and tomato was achieved via knockout of OsHd2 , Hd4 , Hd5 (Li et al ) and of SlSP5G (Soyk et al ), respectively. By contrast, knockout of GmFT2 entailed delayed flowering time in soybean (Cai et al ). Li et al () demonstrated that mutagenesis of the long non‐coding RNA1459 results in delayed tomato fruit ripening.…”
Section: Applications Of Targeted Genome Modification By Nhejmentioning
confidence: 99%
“…In soybean, at least 10 FT homologs have been identified (Kong et al ., ). GmFT2a and GmFT5a were found to be strictly photoperiod‐regulated, and have been shown to promote flowering in Arabidopsis and soybean (Kong et al ., ; Sun et al ., ; Cai et al ., ). The functions of the other GmFTs in soybean remain unclear, although GmFT2b , 3a , 3b , 4 , 5b , and 6 have been preliminarily studied using heterologous expression in Arabidopsis (Fan et al ., ; Zhai et al ., ; Cao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It is thus conceivable that some ratio of a flowering promoter and a flowering inhibitor, as specified by photoperiodic signals, may represent a sort of balance that regulates whether plants undertake vegetative growth or reproductive development In soybean, at least 10 FT homologs have been identified (Kong et al, 2010). GmFT2a and GmFT5a were found to be strictly photoperiod-regulated, and have been shown to promote flowering in Arabidopsis and soybean (Kong et al, 2010;Sun et al, 2011;Cai et al, 2017). The functions of the other GmFTs in soybean remain unclear, although GmFT2b, 3a, 3b, 4, 5b, and 6 have been preliminarily studied using heterologous expression in Arabidopsis (Fan et al, 2014;Zhai et al, 2014;Cao et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports have described the generation of somatic mutations using CRISPR/Cas9 in soya bean (Cai et al, 2015;Du et al, 2016;Jacobs et al, 2015;Lowder et al, 2015;Michno et al, 2015;Tang et al, 2016). To date however, few studies have demonstrated whole-plant soya bean mutagenesis (Cai et al, 2017;Li et al, 2015). Here, we describe a set of plant expression vectors that can accommodate either the CRISPR/Cas9 or TALEN entry vectors to target the genes encoding the machinery proteins involved in small RNA processing in soya bean and M. truncatula Curtin et al, 2017;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%